Political Spiritualities: The Pentecostal Revolution in Nigeria - Marshall, Ruth (University of Chicago Press, 2009)
After an explosion of conversions to Pentecostalism over the past three decades, tens of millions of Nigerians now claim that “Jesus is the answer.” But if Jesus is the answer, what is the question? What led to the movement’s dramatic rise and how can we make sense of its social and political significance? In this ambitiously interdisciplinary study, Ruth Marshall draws on years of fieldwork and grapples with a host of important thinkers—including Foucault, Agamben, Arendt, and Benjamin—to answer these questions. To account for the movement’s success, Marshall explores how Pentecostalism presents the experience of being born again as a chance for Nigerians to realize the promises of political and religious salvation made during the colonial and postcolonial eras. Her astute analysis of this religious trend sheds light on Nigeria’s contemporary politics, postcolonial statecraft, and the everyday struggles of ordinary citizens coping with poverty, corruption, and inequality. Pentecostalism’s rise is truly global, and Political Spiritualities persuasively argues that Nigeria is a key case in this phenomenon while calling for new ways of thinking about the place of religion in contemporary politics.
Paid
Keywords: Religion / Christianity / Pentecostal & Charismatic; Social Science / Anthropology / Cultural & Social; Social Science / General